Epidemiology and clinical study of phenylketonuria (PKU) patients in Khorasan Province; Norteast Iran - Negar Morovatdar; Shapour Badiee Aval; Seyed Mohammad Reza Hosseini Yazdi; Farzaneh Norouzi; Tahereh Mina (Mashhad University of Medical Sciences, 2015)
Epidemiology and clinical study of phenylketonuria (PKU) patients in Khorasan Province; Norteast Iran Background: Phenylketonuria is an autosomal recessive disease. Early diagnosis is a important public health intervention to prevent neurological impairment .This study was designed to describe characteristics of phenylketonouria patients in Khorasan ,Northeast of Iran. Methods: We included all  patients suffering from PKU in khorasan until September 2013. We gathered the variables like diagnosis age , sib of parents, cause of asking physician and screening based diagnosis or clinical based diagnosis. We use descriptive statistics for analysis. Results: The mean age of diagnosis was 19 months .80% pku patients had a positive history of consanguineous marriage in their parents. Incidence of new cases that identified by screening in 2012-2013 was 57 per 1000000 live birth. 10% patients identified with screening in first week of birth. Conclusion: Nearly all of our patients (90%) had been diagnosed without screening in the first days of their life only due to clinical manifestations in the first year of their life . According to efficacy of early diagnosis and dietary treatment, enforcement of public health policy for screening is a critical public health preventive intervention.